New insights into the role of T cells in pathogenesis of psoriasis and psoriatic arthritis. (2nd October 2016) - Karczewski, Jacek; Dobrowolska, Agnieszka; Rychlewska-Hańczewska, Anna; Adamski, Zygmunt
Abstract: Psoriasis is a chronic, relapsing, autoimmune disorder of the skin affecting 2–3% of general population. Approximately 30% of psoriasis patients are also affected with the psoriatic arthritis, a chronic inflammatory spondyloarthritis. The review aims to present the current knowledge on immunopathogenesis of both diseases to emphasize the involvement of various T helper cell subsets. An extensive literature search in electronic databases was performed on the topic of different Th cell subsets' involvement in the pathogenesis of psoriasis and psoriatic arthritis. Studies were assessed and selected to present the recent progress in the area. Current data strongly suggest that both PsO and PsA are T cell-mediated diseases, with a key role of various proinflammatory cytokines in their development. The involvement of T cells is highlighted by the superior efficacy of biologic therapies targeting T cell-derived proinflammatory cytokines in both diseases. Initially, PsO and PsA were thought to be Th1-mediated diseases; however, in the last years, several studies have shown the important role of other T cell subsets, including Th17, Th22, Th9 and Treg cells, in the pathogenesis of both diseases, which has led to the development of new therapies.